TEACHERS’ PREPAREDNESS FOR ACTIVITY IN THE CONTEXT OF INCLUSIVE PRACTICE (Proceedings of the World Disability & Rehabilitation Conference, 2019)
The arrangement of available and quality education for individuals with special educational needs is a necessary condition for such people’s successful socialization in society. The development of inclusion in education is one of the priority directions of public policy in Russia nowadays. However, there are various barriers that hinder inclusive education implementation. One of such barriers is unavailability of teaching staff to work in new conditions. The authors carried out a survey of teachers to reveal difficulties they experience in the course of entering an inclusive environment. Such obstacles as teachers’ insufficient competence in the sphere of psychophysiological features of individuals with special educational needs; lack of technologies aimed to train individuals with special educational needs; psychological unavailability have been revealed. Main professional difficulties that teachers meet working at all stages of training (preschool, school, and higher school) connected with emotional rejection and knowledge of peculiarities of individuals with special educational needs are described. The results of the survey testify to the fact that teachers have embraced ideas and principles of inclusive education in Russia. The obtained data prove the necessity of teachers’ vocational and psychological training for an appropriate work in the conditions of inclusive education.
Keywords: Inclusive education; teachers; individuals with special needs; learners with special educational needs; barriers; professional difficulties